A modular assembly pH-sensitive charge reversal siRNA delivery system. (10th October 2018) - Sun, Qiong; Tang, Chunming; Su, Zhigui; Du, Junjie; Shang, Yunkai; Xue, Lingjing; Zhang, Can
Abstract : Cationic lipids and polymers are the most common non-viral vectors for siRNA delivery; however, their intense positively charged character may give rise to serum-triggered aggregation, immune activation, inflammation stimulation and grievous toxicity. Abstract : Cationic lipids and polymers are the most common non-viral vectors for siRNA delivery; however, their intense positively charged character may give rise to serum-triggered aggregation, immune activation, inflammation stimulation and grievous toxicity. An ocean of charge shielding strategies is exploited, but the currently available siRNA delivery systems still remain ungratified and deficient. Herein, we developed a facile modular assembly strategy for a pH-sensitive charge reversal siRNA delivery system (PC), which can be easily obtained by adjusting the ratios of positively and negatively charged modules. This PC is electronegative at neutral pH and reverses to electropositive at an acidic pH value with increased tumor cellular uptake. Also, the PC can promote efficient intracellular release and cytoplasmic distribution of siRNA, due to its fusogenic potential with the lysosome membrane. Moreover, the PC loaded with siRNA targeting survivin mRNA (cpusiRNA2) specifically down-regulated the expression of survivin, possessing remarkable tumor therapeutic efficacy in vitro and in vivo . Accordingly, this handy and effective assembly strategy would provide a promising platform for the design of siRNA delivery systems in cancer therapy.